PENGARUH EDUKASI VIDEO ANIMASI SADARI TERHADAP PELAKSANAAN SADARI PADA SANTRIWATI MAS MADINATUL MUNAWWAROH BUKITTINGGI - Afnas, Nur Hidayah; Azhari, Armita Sri; Sa’danoer, Ira Maulina (Ensiklopedia of Journal, 2025)
The influence of animated video education on improving the implementation of BSE in female students at MAS Madinatul Munawwaroh Bukittinggi Currently, breast cancer is a serious threat in the world and is also a major problem in Indonesia and other countries. Breast cancer is a major cause of morbidity and mortality among women. The World Health Organization (WHO) estimates that in 2020, there will be 2.3 million women diagnosed with breast cancer and 685,000 deaths globally. By the end of 2020, there were 7.8 million women diagnosed with breast cancer in the last 5 years, making breast cancer the most common cancer in the world. This study aims to determine the Effect of Providing Education About BSE on the Implementation of BSE in female students of MAS Madinatul Munawwaroh Bukittinggi. This type of research is quantitative research with a Quasi Experiment design with a One Group Pretest Posttest design. The population in this study were all female students of MAS Madinatul Munawwaroh with a sample of 25 students from grades XI and XII who were given an animated video intervention about BSE. Sampling in this study used the Total Sampling technique. The research instrument used a questionnaire and the data was processed univariately and bivariately. In this study, the results obtained were the average implementation of BSE before being given education about BSE was 0.08, the average implementation of BSE after being given education about BSE was 3.00. The results of the statistical test obtained a p value of 0.000. The conclusion of this study is the influence of providing education about BSE on the implementation of BSE in female students of MAS Madinatul Munawwaroh Bukittinggi. Suggestions are expected that MAS Madinatul Munawaaroh Bukittinggi will continue to facilitate its female students in gaining knowledge about health, especially about breast cancer prevention..Keywords: Education; video; BSE; implementation of BSE